PENERAPAN MODEL PEMBELAJARAN MASTERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS V SD NEGERI 017 BAGAN LIMAU KECAMATAN UKUI - Edi Mohamad Muhtar (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The low yield learning civics class V students of SD Negeri 017 Bagan Limau This is thebackground of this research. This research was conducted aims to improve learning outcomesCivics through mastery learning model learning. This research is a class act, carried out bytwo cycles. The data used in this research is data result of learning civics. Based on theresults of the study revealed that learning outcomes Civics increased, this is evidenced by: (a)the preliminary data of students who achieve mastery only 50% and cycle to the first increasehas reached 76% and the thoroughness of the class in the second cycle at 90%; and (b) theresults of learning civics students also increased at an average baseline value of 65 students,the first cycle to 68.25 and the second cycle increased to 74.5. Therefore it can be concludedthat the learning model of mastery learning can improve learning outcomes Civics class Vstudents of SD Negeri 017 Bagan Limau.